Silencer - Wicker, Marcus (Boston : Mariner Books, 2017)
"Welcome to Marcus Wicker's Midwest, where the muzzle is always on and where silence and daily microaggressions can chafe away at the faith of a young man grieved by images of gun violence and police brutality in twenty-first-century America. Precisely contradictory, bittersweet, witty, and heartbreaking, Silencer is where the political and the personal collide. Driven by the sounds of hip-hop and reimagined forms and structures, Wicker's explosive second bookis composed of poems at war with themselves, verses in which the poet questions his own faith in God, in hope, in the American Dream, and in himself. Pushing our ideas of traditions and expectations, these poems and queries work in concert towards creating a new dialectic"--
Keywords: POETRY / American / African American; POETRY / Inspirational & Religious; POETRY / American / General; HISTORY / Social History; SOCIAL SCIENCE / Black Studies (Global)